IMPACT OF ENVIRONMENTAL PROBLEMS ON ECONOMIC SECURITY - Bahodirov Zokirjon (Journals Park Publishing, 2022)
This article provides information on the impact of various environmental problems on economic security, environmental security and environmental threats, including green economy, principles of green economy, and solutions to environmental problems and countermeasures in the Republic of Uzbekistan. and offers are made.
Keywords: Environmental problems, environmental threats, economic security, green economy, principles of green economy, healthy planet, sustainable consumption and production, ecology, environmental destruction, demographic explosion